2020
DOI: 10.1021/acsami.9b18098
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Graphene Hydrogel Decorated with SnO2 for High-Performance NO2 Sensing with Enhanced Immunity to Humidity

Abstract: A facile, one-step hydrothermal route was exploited to prepare SnO2-decorated reduced graphene oxide hydrogel (SnO2/RGOH) with three-dimensional (3D) porous structures for NO2 gas detection. Various material characterizations demonstrate the effective deoxygenation of graphene oxide and in situ growth of rutile SnO2 nanoparticles (NPs) on 3D RGOH. Compared with the pristine RGOH, the SnO2/RGOH displayed much lower limit of detection (LOD) and an order of magnitude higher sensitivity, revealing the distinct imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 61 publications
0
64
0
Order By: Relevance
“…Li and co-workers used SnO 2 nanocrystals supported by the 3D mesoporous graphene aerogels to detect NO 2 gas at low temperature [ 84 ]. Wu et al [ 85 ] reported a facile preparation of SnO 2 -modified graphene hydrogel (SnO 2 /RGOH) via the one-step hydrothermal method. 3D SnO 2 /RGOH was synthesized directly from Sn 2+ and GO precursors without any surfactant.…”
Section: No 2 Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li and co-workers used SnO 2 nanocrystals supported by the 3D mesoporous graphene aerogels to detect NO 2 gas at low temperature [ 84 ]. Wu et al [ 85 ] reported a facile preparation of SnO 2 -modified graphene hydrogel (SnO 2 /RGOH) via the one-step hydrothermal method. 3D SnO 2 /RGOH was synthesized directly from Sn 2+ and GO precursors without any surfactant.…”
Section: No 2 Gas Sensorsmentioning
confidence: 99%
“… ( a ) SEM image of 3D SnO 2 /RGOH; ( b ) Dynamic responses of RGOH and SnO 2 /RGOH to NO 2 ; ( c ) RT responses of SnO 2 /RGOH and RGOH; ( d ) Real-time responses of the flexible SnO 2 /RGOH sensor. Inset: Photograph of the sensor with the bent angle of 150° [ 85 ]. …”
Section: Figurementioning
confidence: 99%
“…Note that two‐dimensional (2D) reduced graphene oxide (RGO) sheets can be self‐ assembled into three‐dimensional (3D) graphene hydrogels with a porous structure, high specific surface area and unique properties via a one‐step, facile hydrothermal approach without the requirement of external templates. [ 30–33 ] Recently, 3D structured and porous graphene has been extensively investigated and employed for high‐performance chemical sensing, energy storage and electrochemical applications, etc., due to their increased surface to volume ratio, abundant reactive sites, and enhanced charge/mass/thermal transfer compared with the 2D counterpart. [ 34–37 ] However, most of the graphene‐based temperature sensors focus on 2D graphene/RGO sheets and their composites, leaving the thermal sensing properties of 3D graphene unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several shortcomings of pure SnO 2 -based sensors that limit their practical applications. Firstly, aggregation occurs when the size is too small during the material synthesis and the sensor fabrication processes, which decreases the surface-specific area, reduces the sensitivity of gas sensors and influences the longterm stability of the as-fabricated sensor (Li, et al, 2015;Wu, et al, 2020). Meanwhile, the SnO 2 -based gas sensor generally needs a high operation temperature (>200°C) to achieve high sensitivity, which causes high power consumption (Van Hieu, 2010;.…”
Section: Introductionmentioning
confidence: 99%